Optical glass and optical components
Through reasonable design of optical glass components, optimizing the ratio of Al2O3/TIO2, solving the problem of poor performance of the existing optical glass anticompores, realizing high hardness and excellent anticorbine performance, and extending the service life of the glass.
Patent Information
- Application Number
- CN202410615939.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-17
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-05-17
AI Technical Summary
The existing optical glass with a refractive index of 1.86 to 1.91 and an ABE number of 37 to 41 has the problem of poor crystallization resistance, which affects its performance and service life.
Through reasonable design of optical glass components, containing SIO2: 4-11 %, B2O3: 8-15 %, LA2O3: 45 % to 55 %, GD2O3: 2 ~ 9.5 %, Y2O3: 4 ~ 10 %, ZRO2: 3 ~ 3 ~ 10 % NB2O5: 5 ~ 12 %, TIO2: 0.1 ~ 5 %, Al2O3: 0 to 4 %, and control the ratio of Al2O3/TIO2 in the range of 0.05 to 3.0, optimizing the hardness and anticorbine performance of the glass.
The performance of excellent anti -ingredients and high hardness of optical glass, extending the service life of glass and improving its application performance in the fields of vehicle imaging, monitoring security.
Smart Images

Figure BDA0004845236810000191 
Figure BDA0004845236810000211 
Figure BDA0004845236810000221
Abstract
Description
Technical Field
[0001] The invention relates to an optical glass, in particular to an optical glass with excellent anti-crystallization performance and high hardness. Background Art
[0002] In recent years, with the continuous integration of optics, electronic information science and new materials science, the application of optical glass as the basic material of optoelectronics in technical fields such as optical transmission, optical storage and optoelectronic display has developed rapidly. Optical instruments have developed rapidly in digitalization, integration and high precision, and higher requirements have been put forward for the performance of optical glass used in optical instruments and equipment. Optical glass with a refractive index of 1.86-1.91 and an Abbe number of 37-41 has a high refractive index, which is of great significance in simplifying optical systems and improving imaging quality in the fields of optical design and optical communication. In the prior art, optical glasses with a refractive index of 1.86-1.91 and an Abbe number of 37-41 generally have poor anti-crystallization performance. During the glass melting process or the glass in the secondary precision pressing process, crystallization is easy to occur inside or on the surface of the glass, resulting in reduced performance or even scrapping of the glass. On the other hand, with the rapid development of vehicle-mounted imaging, monitoring and security and other fields, the demand for high refractive index and low dispersion optical glass in related fields continues to increase. Optical glass used in the fields of vehicle-mounted imaging, monitoring and security is expected to have a higher hardness to resist the wear or impact of sand and stones during vehicle driving, improve the impact resistance of the glass, and extend the service life of the optical glass. Summary of the invention
[0003] Based on the above reasons, the technical problem to be solved by the present invention is to provide an optical glass with excellent anti-crystallization performance and high hardness.
[0004] The technical solution adopted by the present invention to solve the technical problem is:
[0005] (1) Optical glass, the components of which, expressed in percentage by weight, contain: SiO2: 4-11%; B2O3: 8-15%; La2O3: greater than 45% but less than or equal to 55%; Gd2O3: 2-9.5%; Y2O3: 4-10%; ZrO2: 3-10%; Nb2O5: 5-12%; TiO2: 0.1-5%; Al2O3: greater than 0 but less than or equal to 4%, wherein the ratio of Al2O3 to TiO2 is 0.05-3.0.
[0006] (2) The optical glass according to (1), wherein the components, expressed in weight percentage, further contain: ZnO: 0-4%; and / or RO: 0-5%; and / or Rn2O: 0-5%; and / or WO3: 0-5%; and / or Ta2O5: 0-5%; and / or Yb2O3: 0-5%; and / or GeO2: 0-4%; and / or clarifier: 0-1%, wherein RO is one or more of MgO, CaO, SrO, and BaO, Rn2O is one or more of Li2O, Na2O, and K2O, and the clarifier is one or more of Sb2O3, SnO2, and CeO2.
[0007] (3) Optical glass, comprising SiO2, B2O3, La2O3, Gd2O3, Y2O3, ZrO2, Nb2O5, TiO2 and Al2O3, wherein the composition is expressed in weight percentage, wherein Al2O3 / TiO2 is 0.05 to 3.0, and the Knoop hardness of the optical glass is H K 680×10 7 Pa or above, and the anti-crystallization performance is above Class C.
[0008] (4) The optical glass according to (3), wherein the components, expressed in weight percentage, are: SiO2: 4-11%; and / or B2O3: 8-15%; and / or La2O3: greater than 45% but less than or equal to 55%; and / or Gd2O3: 2-9.5%; and / or Y2O3: 4-10%; and / or ZrO2: 3-10%; and / or Nb2O5: 5-12%; and / or TiO2: 0.1-5%; and / or Al2O3: greater than 0 but less than or equal to 4%; and / or ZnO: 0-4%; and / or RO: 0-5%; and / or Rn2O: 0-5%; and / or WO3: 0-5%; and / or Ta2O5: 0-5%; and / or Yb2O3: 0-5%; and / or GeO2: 0-4%; and / or clarifier: 0-1%, wherein RO is one or more of MgO, CaO, SrO, and BaO, Rn2O is one or more of Li2O, Na2O, and K2O, and the clarifier is one or more of Sb2O3, SnO2, and CeO2.
[0009] (5) The optical glass according to any one of (1) to (4), wherein the components thereof, expressed in weight percentage, satisfy one or more of the following 11 conditions:
[0010] 1) Gd2O3 / Y2O3 is 0.25 to 1.1, preferably Gd2O3 / Y2O3 is 0.3 to 1.0, more preferably Gd2O3 / Y2O3 is 0.4 to 0.9, and further preferably Gd2O3 / Y2O3 is 0.5 to 0.9;
[0011] 2) Gd2O3 / SiO2 is 0.2 to 1.0, preferably Gd2O3 / SiO2 is 0.3 to 0.95, more preferably Gd2O3 / SiO2 is 0.4 to 0.9, and further preferably Gd2O3 / SiO2 is 0.5 to 0.9;
[0012] 3) Al2O3 / TiO2 is 0.1 to 2.0, preferably Al2O3 / TiO2 is 0.1 to 1.5, and more preferably Al2O3 / TiO2 is 0.2 to 1.0;
[0013] 4) (La2O3+Y2O3) / (Nb2O5+ZrO2) is 2.5 to 6.5, preferably (La2O3+Y2O3) / (Nb2O5+ZrO2) is 2.8 to 6.0, more preferably (La2O3+Y2O3) / (Nb2O5+ZrO2) is 3.0 to 5.5, and further preferably (La2O3+Y2O3) / (Nb2O5+ZrO2) is 3.5 to 5.0;
[0014] 5) Al2O3 / Gd2O3 is 0.02 to 0.8, preferably Al2O3 / Gd2O3 is 0.05 to 0.6, more preferably Al2O3 / Gd2O3 is 0.1 to 0.5, and further preferably Al2O3 / Gd2O3 is 0.1 to 0.4;
[0015] 6) (La2O3+Nb2O5) / Gd2O3 is 6.0 to 23.0, preferably (La2O3+Nb2O5) / Gd2O3 is 8.0 to 20.0, more preferably (La2O3+Nb2O5) / Gd2O3 is 9.0 to 15.0, and further preferably (La2O3+Nb2O5) / Gd2O3 is 10.0 to 13.0;
[0016] 7) Nb2O5 / Y2O3 is 0.6 to 2.0, preferably Nb2O5 / Y2O3 is 0.7 to 1.7, more preferably Nb2O5 / Y2O3 is 0.8 to 1.5, and further preferably Nb2O5 / Y2O3 is 0.9 to 1.2;
[0017] 8) Al2O3 / SiO2 is 0.01 to 0.8, preferably Al2O3 / SiO2 is 0.05 to 0.6, more preferably Al2O3 / SiO2 is 0.08 to 0.5, and further preferably Al2O3 / SiO2 is 0.1 to 0.3;
[0018] 9) Y2O3 / (Gd2O3+Ta2O5+ZnO+WO3+GeO2) is 0.9 to 4.0, preferably Y2O3 / (Gd2O3+Ta2O5+ZnO+WO3+GeO2) is 1.0 to 3.5, more preferably Y2O3 / (Gd2O3+Ta2O5+ZnO+WO3+GeO2) is 1.0 to 3.0, and further preferably Y2O3 / (Gd2O3+Ta2O5+ZnO+WO3+GeO2) is 1.2 to 2.0;
[0019] 10) (TiO2+ZnO+Ta2O5+WO3) / Nb2O5 is 0.01 to 1.0, preferably (TiO2+ZnO+Ta2O5+WO3) / Nb2O5 is 0.05 to 0.8, more preferably (TiO2+ZnO+Ta2O5+WO3) / Nb2O5 is 0.1 to 0.5, and further preferably (TiO2+ZnO+Ta2O5+WO3) / Nb2O5 is 0.1 to 0.3;
[0020] 11) (Ta2O5+ZnO+RO) / TiO2 is less than 2.5, preferably (Ta2O5+ZnO+RO) / TiO2 is less than 1.5, more preferably (Ta2O5+ZnO+RO) / TiO2 is less than 1.0, and further preferably (Ta2O5+ZnO+RO) / TiO2 is less than 0.5,
[0021] The RO is one or more of MgO, CaO, SrO and BaO.
[0022] (6) The optical glass according to any one of (1) to (4), wherein the components are expressed in weight percentage, wherein: SiO2: 5 to 10%, preferably SiO2: 5.5 to 9%; and / or B2O3: 10 to 14%, preferably B2O3: 11 to 13.5%; and / or La2O3: 46 to 53%, preferably La2O3: 48 to 52%; and / or Gd2O3: 3 to 8%, preferably Gd2 O3: 4-7%; and / or Y2O3: 5-9.5%, preferably Y2O3: 5.5-8.5%; and / or ZrO2: 4-9%, preferably ZrO2: 5-8%; and / or Nb2O5: 5.5-11%, preferably Nb2O5: 6-10%; and / or TiO2: 0.5-4%, preferably TiO2: 1-3%; and / or Al2O3: 0.1-3%, preferably Al2O 3: 0.5-2%; and / or ZnO: 0-2%, preferably ZnO: 0-1%; and / or RO: 0-3%, preferably RO: 0-1%; and / or Rn2O: 0-3%, preferably Rn2O: 0-1%; and / or WO3: 0-3%, preferably WO3: 0-1%; and / or Ta2O5: 0-3%, preferably Ta2O5: 0-1%; and / or Yb2O3: 0-3%, preferably Yb2O3: 0-1%; and / or GeO2: 0-2%, preferably GeO2: 0-1%; and / or clarifier: 0-0.5%, preferably clarifier: 0-0.1%, wherein RO is one or more of MgO, CaO, SrO and BaO, Rn2O is one or more of Li2O, Na2O and K2O, and clarifier is one or more of Sb2O3, SnO2 and CeO2.
[0023] (7) The optical glass according to any one of (1) to (4), which does not contain ZnO; and / or does not contain MgO; and / or does not contain CaO; and / or does not contain SrO; and / or does not contain BaO; and / or does not contain Li2O; and / or does not contain Na2O; and / or does not contain K2O; and / or does not contain WO3; and / or does not contain Ta2O5; and / or does not contain Yb2O3; and / or does not contain GeO2; and / or does not contain Sb2O3; and / or does not contain SnO2; and / or does not contain CeO2.
[0024] (8) The optical glass according to any one of (1) to (4), wherein the refractive index of the optical glass is n d is 1.86 to 1.91, preferably 1.87 to 1.90, more preferably 1.875 to 1.89; Abbe number v d It is 37-41, preferably 38-40.5, and more preferably 38.5-40.
[0025] (9) The optical glass according to any one of (1) to (4), wherein the thermal expansion coefficient of the optical glass is -30 / 70℃ 85×10 -7 / K or less, preferably 80×10 -7 / K or less, more preferably 75×10 -7 / K or less; and / or water resistance stability D W 2 or more, preferably 1; and / or acid resistance stability D A 2 or more, preferably 1; and / or Knoop hardness H K 680×10 7 Pa or more, preferably 690×10 7 Pa or more, more preferably 700×10 7 Pa or above; and / or relative partial dispersion P g,F is 0.7000 or less, preferably 0.6500 or less, more preferably 0.6000 or less; and / or relative partial dispersion deviation value ΔP g,F The molecular weight of the present invention is -0.0020 or less, preferably -0.0040 or less, more preferably -0.0050 or less, and further preferably -0.0058 or less; and / or the bubble degree is A grade or above, preferably A0 grade or above, and more preferably A 00 and / or a stripe degree of C or above, preferably B or above; and / or a density ρ of 5.10g / cm 3 Below, preferably 5.00 g / cm 3 Below, more preferably 4.95g / cm 3 and / or the anti-crystallization performance is C grade or above, preferably B grade or above, more preferably A grade.
[0026] (10) A glass preform made of any optical glass described in (1) to (9).
[0027] (11) An optical element made of the optical glass described in any one of (1) to (9), or made of the glass preform described in (10).
[0028] (12) An optical instrument comprising the optical glass described in any one of (1) to (9) and / or the optical element described in (11).
[0029] The beneficial effects of the present invention are: through reasonable component design, the optical glass of the present invention has excellent anti-crystallization performance and higher hardness. DETAILED DESCRIPTION
[0030] The following will describe the embodiments of the optical glass of the present invention in detail, but the present invention is not limited to the following embodiments, and can be implemented by appropriate changes within the scope of the purpose of the present invention. In addition, although there are appropriate omissions of descriptions of the repeated descriptions, the gist of the invention will not be limited thereby, and in the following content, the optical glass of the present invention is sometimes referred to as glass.
[0031] [Optical glass]
[0032] The following is an explanation of the range of each component (ingredient) of the optical glass of the present invention. In the present invention, unless otherwise specified, the content and total content of each component are all expressed in weight percentage (wt%), that is, the content and total content of each component are expressed in weight percentage relative to the total amount of glass material converted into oxide composition. Here, the "composition converted into oxide" means that when the oxides, complex salts and hydroxides used as raw materials for the optical glass components of the present invention decompose and transform into oxides during melting, the total amount of the oxide material is taken as 100%.
[0033] Unless otherwise specified in specific circumstances, the numerical ranges listed in the present invention include upper and lower limits, "above" and "below" include endpoint values, and all integers and fractions included in the range, without being limited to the specific values listed when the range is defined. "And / or" referred to herein is inclusive, for example, "A and / or B" means only A, or only B, or both A and B.
[0034] <Essential Components and Optional Components>
[0035] SiO2 can increase the viscosity of molten glass, reduce the coloring of glass, improve the thermal stability of glass, and improve the resistance to devitrification, but if its content is too high, the melting difficulty of glass increases, the transition temperature increases, and the refractive index is difficult to meet the design requirements. Therefore, the content of SiO2 in the present invention is 4-11%, preferably 5-10%, and more preferably 5.5-9%. In some embodiments, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11% SiO2 may be included.
[0036] B2O3 is a glass network forming component, which can improve the solubility and resistance to devitrification of glass. It is also an effective component for giving glass low dispersion. If its content is less than 8%, the stability of the glass is reduced. If the content of B2O3 is too high, the chemical stability of the glass is reduced, and the refractive index of the glass is difficult to meet the design requirements. Therefore, the content of B2O3 in the present invention is 8-15%, preferably 10-14%, and more preferably 11-13.5%. In some embodiments, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15% B2O3 may be included.
[0037] La2O3 is a high-refractive, low-dispersion component that can increase the refractive index of glass and adjust dispersion, and reduce the high-temperature viscosity of glass. If its content is too high, the resistance to devitrification of the glass will decrease, and the temperature coefficient of refractive index and the Abbe number will be difficult to meet the design requirements. Therefore, the content of La2O3 in the present invention is greater than 45% but less than or equal to 55%, preferably 46-53%, and more preferably 48-52%. In some embodiments, greater than 45%, 45.1%, 45.5%, 46%, 46.5%, 47%, 47.5%, 48%, 48.5%, 49%, 49.5%, 50%, 50.5%, 51%, 51.5%, 52%, 52.5%, 53%, 53.5%, 54%, 54.5%, 55% La2O3 may be included.
[0038] Gd2O3 is a high refractive and low dispersion component. It can reduce the relative partial dispersion of glass and improve chemical stability in glass. If its content is too high, the devitrification resistance of glass will deteriorate and the transition temperature will increase. Therefore, the content of Gd2O3 in the present invention is 2-9.5%, preferably 3-8%, and more preferably 4-7%. In some embodiments, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5% Gd2O3 may be included.
[0039] In some embodiments, the ratio of the content of Gd2O3 to the content of SiO2, Gd2O3 / SiO2, is controlled within the range of 0.2 to 1.0, so that the optical glass can have excellent chemical stability while improving the hardness and bubble degree of the glass and preventing the increase of the thermal expansion coefficient. Therefore, Gd2O3 / SiO2 is preferably 0.2 to 1.0, more preferably 0.3 to 0.95, further preferably 0.4 to 0.9, and further preferably 0.5 to 0.9. In some embodiments, the value of Gd2O3 / SiO2 may be 0.2, 0.23, 0.25, 0.27, 0.3, 0.33, 0.35, 0.37, 0.4, 0.43, 0.45, 0.47, 0.5, 0.53, 0.55, 0.57, 0.6, 0.63, 0.65, 0.67, 0.7, 0.73, 0.75, 0.77, 0.8, 0.83, 0.85, 0.87, 0.9, 0.93, 0.95, 0.97, or 1.0.
[0040] In the present invention, by containing more than 4% Y2O3 and by combining Y2O3 with Gd2O3, the meltability and anti-crystallization property of the glass are improved while maintaining a high refractive index and low dispersion. If the content of Y2O3 is too high, the stability and resistance to devitrification of the glass are reduced, and the transition temperature is increased. Therefore, the content of Y2O3 is 4 to 10%, preferably 5 to 9.5%, and more preferably 5.5 to 8.5%. In some embodiments, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, and 10% Y2O3 may be included.
[0041] In some embodiments, the ratio of the content of Gd2O3 to the content of Y2O3, Gd2O3 / Y2O3, is controlled within the range of 0.25 to 1.1, which can reduce the thermal expansion coefficient of the glass and improve the chemical stability of the glass. Therefore, Gd2O3 / Y2O3 is preferably 0.25 to 1.1, and Gd2O3 / Y2O3 is more preferably 0.3 to 1.0. Further, controlling Gd2O3 / Y2O3 within the range of 0.4 to 0.9 can further improve the anti-crystallization performance of the glass. Therefore, it is further preferred that Gd2O3 / Y2O3 is 0.4 to 0.9, and it is further preferred that Gd2O3 / Y2O3 is 0.5 to 0.9. In some embodiments, the value of Gd2O3 / Y2O3 may be 0.25, 0.27, 0.3, 0.33, 0.35, 0.37, 0.4, 0.43, 0.45, 0.47, 0.5, 0.53, 0.55, 0.57, 0.6, 0.63, 0.65, 0.67, 0.7, 0.73, 0.75, 0.77, 0.8, 0.83, 0.85, 0.87, 0.9, 0.93, 0.95, 0.97, 1.0, 1.03, 1.05, 1.07, 1.1.
[0042] Yb2O3 is a high-refractive, low-dispersion component. If its content exceeds 5%, the anti-crystallization performance of the glass decreases. Therefore, the content of Yb2O3 is 0-5%, preferably 0-3%, more preferably 0-1%, and further preferably no Yb2O3. In some embodiments, 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% Yb2O3 may be included.
[0043] ZrO2 can increase the refractive index and devitrification resistance of glass and reduce the ΔP of glass. g,F value, improves the chemical stability and mechanical properties of the glass. If its content is too high, the melting difficulty of the glass increases, which easily leads to inclusions inside the glass and a decrease in light transmittance, while reducing the anti-crystallization performance of the glass. Therefore, the content of ZrO2 in the present invention is 3-10%, preferably 4-9%, and more preferably 5-8%. In some embodiments, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10% ZrO2 may be included.
[0044] Nb2O5 has the function of increasing the refractive index, improving chemical stability and resistance to devitrification, and can reduce the thermal expansion coefficient of glass without significantly increasing P g,F Value and ΔP g,FValue, if its content is less than 5%, the above effect is not obvious. If the content of Nb2O5 exceeds 12%, the weather resistance and light transmittance of the glass decrease, and the transition temperature of the glass increases. Therefore, the content of Nb2O5 is 5-12%, preferably 5.5-11%, and more preferably 6-10%. In some embodiments, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12% Nb2O5 may be included.
[0045] In some embodiments, the ratio of the total content of La2O3 and Y2O3 La2O3+Y2O3 to the total content of Nb2O5 and ZrO2 Nb2O5+ZrO2 (La2O3+Y2O3) / (Nb2O5+ZrO2) is controlled within the range of 2.5 to 6.5, so that the optical glass can more easily obtain the desired refractive index and Abbe number, and reduce the P of the glass. g,F Value and ΔP g,F value. Therefore, it is preferred that (La2O3+Y2O3) / (Nb2O5+ZrO2) is 2.5~6.5, and it is more preferred that (La2O3+Y2O3) / (Nb2O5+ZrO2) is 2.8~6.0. Furthermore, by controlling (La2O3+Y2O3) / (Nb2O5+ZrO2) within the range of 3.0~5.5, the hardness of the glass can be further improved. Therefore, it is further preferred that (La2O3+Y2O3) / (Nb2O5+ZrO2) is 3.0~5.5, and it is further preferred that (La2O3+Y2O3) / (Nb2O5+ZrO2) is 3.5~5.0. In some embodiments, the value of (La2O3+Y2O3) / (Nb2O5+ZrO2) may be 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.8, 5.9, 6.0, 6.1, 6.2, 6.3, 6.4, 6.5.
[0046] In some embodiments, the ratio of the total content of La2O3 and Nb2O5 La2O3 + Nb2O5 to the content of Gd2O3 (La2O3 + Nb2O5) / Gd2O3 is controlled within the range of 6.0 to 23.0, which can reduce the density of the glass, P g,F Value and ΔP g,FTherefore, the (La2O3+Nb2O5) / Gd2O3 is preferably 6.0 to 23.0, more preferably 8.0 to 20.0, further preferably 9.0 to 15.0, and further preferably 10.0 to 13.0. In some embodiments, the value of (La2O3+Nb2O5) / Gd2O3 may be 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0, 10.5, 11.0, 11.5, 12.0, 12.5, 13.0, 13.5, 14.0, 14.5, 15.0, 15.5, 16.0, 16.5, 17.0, 17.5, 18.0, 18.5, 19.0, 19.5, 20.0, 20.5, 21.0, 21.5, 22.0, 22.5, 23.0.
[0047] In some embodiments, the ratio of Nb2O5 to Y2O3 is controlled within the range of 0.6 to 2.0, so that the optical glass can have a desired refractive index and Abbe number while improving the bubble degree of the glass and preventing the reduction of weather resistance and devitrification resistance. Therefore, Nb2O5 / Y2O3 is preferably 0.6 to 2.0, more preferably 0.7 to 1.7, further preferably 0.8 to 1.5, and further preferably 0.9 to 1.2. In some embodiments, the value of Nb2O5 / Y2O3 may be 0.6, 0.63, 0.65, 0.67, 0.7, 0.73, 0.75, 0.77, 0.8, 0.83, 0.85, 0.87, 0.9, 0.93, 0.95, 0.97, 1.0, 1.03, 1.05, 1.07, 1.1, 1.13, 1.15, 1.17, 1.2, 1.23, 1.25, 1.27, 1.3, 1.33, 1.35, 1.37, 1.4, 1.43, 1.45, 1.47, 1.5, 1.53, 1.55, 1.57, 1.6, 1.63, 1.65, 1.67, 1.7, 1.73, 1.75, 1.77, 1.8, 1.83, 1.85, 1.87, 1.9, 1.93, 1.95, 1.97, 2.0.
[0048] Al2O3 can reduce the thermal expansion coefficient of glass and improve the anti-crystallization and thermal stability of glass. However, if the Al2O3 content is too high, the glass transition temperature will increase and the solubility of the glass will deteriorate. Therefore, the content of Al2O3 in the present invention is greater than 0 but less than or equal to 4%, preferably 0.1-3%, and more preferably 0.5-2%. In some embodiments, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4% Al2O3 may be included.
[0049] In some embodiments, the ratio of Al2O3 to SiO2, Al2O3 / SiO2, is controlled within the range of 0.01 to 0.8, which can improve the anti-crystallization performance and striae of the glass and optimize the abrasiveness of the glass. Therefore, Al2O3 / SiO2 is preferably 0.01 to 0.8, more preferably 0.05 to 0.6, further preferably 0.08 to 0.5, and further preferably 0.1 to 0.3. In some embodiments, the value of Al2O3 / SiO2 may be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.13, 0.15, 0.17, 0.2, 0.23, 0.25, 0.27, 0.3, 0.33, 0.35, 0.37, 0.4, 0.43, 0.45, 0.47, 0.5, 0.53, 0.55, 0.57, 0.6, 0.63, 0.65, 0.67, 0.7, 0.73, 0.75, 0.77, 0.8.
[0050] In some embodiments, the ratio of Al2O3 to Gd2O3 is controlled within the range of 0.02 to 0.8, which can improve the striation and hardness of the glass and optimize the anti-devitrification property of the glass. Therefore, Al2O3 / Gd2O3 is preferably 0.02 to 0.8, more preferably 0.05 to 0.6, further preferably 0.1 to 0.5, and further preferably 0.1 to 0.4. In some embodiments, the value of Al2O3 / Gd2O3 may be 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.13, 0.15, 0.17, 0.2, 0.23, 0.25, 0.27, 0.3, 0.33, 0.35, 0.37, 0.4, 0.43, 0.45, 0.47, 0.5, 0.53, 0.55, 0.57, 0.6, 0.63, 0.65, 0.67, 0.7, 0.73, 0.75, 0.77, 0.8.
[0051] TiO2 has the function of increasing the refractive index and dispersion of glass. The appropriate amount of TiO2 in the present invention can increase the stability of glass and improve the anti-crystallization performance of glass. However, if the content exceeds 5%, the P g,F Value and ΔP g,F The value becomes larger, and the glass is easy to crystallize during the pressing process. Therefore, the content of TiO2 in the present invention is 0.1-5%, preferably 0.5-4%, and more preferably 1-3%. In some embodiments, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% TiO2 may be included.
[0052] In some embodiments, the ratio of Al2O3 to TiO2 is controlled within the range of 0.05 to 3.0, which can improve the anti-devitrification performance and hardness of the glass and optimize the striation of the glass. Therefore, Al2O3 / TiO2 is preferably 0.05 to 3.0, more preferably 0.1 to 2.0, further preferably 0.1 to 1.5, and further preferably 0.2 to 1.0. In some embodiments, the value of Al2O3 / TiO2 may be 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1. 0, 1.05, 1.1, 1.15, 1.2, 1.25, 1.3, 1.35, 1.4, 1.45, 1.5, 1.55, 1.6, 1.65, 1.7, 1.75, 1.8, 1.85, 1.9, 1.95, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0.
[0053] ZnO is an optional component of the present invention, which can improve the chemical stability of glass, enhance the weather resistance of glass, and reduce the transition temperature of glass. However, when its content is too high, it will increase the corrosion of platinum utensils during smelting, reduce the service life of the furnace, and be unfavorable to the anti-devitrification of glass. Therefore, the content of ZnO in the present invention is 0-4%, preferably 0-2%, more preferably 0-1%, and further preferably does not contain ZnO. In some embodiments, 0%, greater than 0%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4% ZnO may be included.
[0054] WO3 can improve the refractive index and mechanical strength of glass. If the content of WO3 exceeds 5%, the thermal stability of glass decreases and the resistance to devitrification decreases. Therefore, the content of WO3 in the present invention is 0-5%, preferably 0-3%, and more preferably 0-1%. In some embodiments, it is further preferred that WO3 is not contained. In some embodiments, 0%, greater than 0%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% WO3 may be included.
[0055] Ta2O5 has the effect of increasing the refractive index of glass and improving the resistance to devitrification, but if its content is too high, the thermal stability of the glass decreases, the density increases, and the cost control of the glass raw materials is unfavorable. Therefore, the content of Ta2O5 in the present invention is 0-5%, preferably 0-3%, and more preferably 0-1%. In some embodiments, it is further preferred that Ta2O5 is not contained. In some embodiments, 0%, greater than 0%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% of Ta2O5 may be included.
[0056] In some embodiments, the ratio of the total content of TiO2, ZnO, Ta2O5, and WO3 to the content of Nb2O5 (TiO2+ZnO+Ta2O5+WO3) / Nb2O5 is controlled within the range of 0.01 to 1.0, which can reduce the thermal expansion coefficient of the glass, increase the bubble degree of the glass, and prevent P g,F Value and ΔP g,FThe value becomes larger. Therefore, it is preferred that (TiO2+ZnO+Ta2O5+WO3) / Nb2O5 is 0.01 to 1.0, and it is more preferred that (TiO2+ZnO+Ta2O5+WO3) / Nb2O5 is 0.05 to 0.8, and it is further preferred that (TiO2+ZnO+Ta2O5+WO3) / Nb2O5 is 0.1 to 0.5, and it is further preferred that (TiO2+ZnO+Ta2O5+WO3) / Nb2O5 is 0.1 to 0.3. In some embodiments, the value of (TiO2+ZnO+Ta2O5+WO3) / Nb2O5 may be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.13, 0.15, 0.17, 0.2, 0.23, 0.25, 0.27, 0.3, 0.3 3, 0.35, 0.37, 0.4, 0.43, 0.45, 0.47, 0.5, 0.53, 0.55, 0.57, 0.6, 0.63, 0.65, 0.67, 0.7, 0.73, 0.75, 0.77, 0.8, 0.83, 0.85, 0.87, 0.9, 0.93, 0.95, 0.97, 1.0.
[0057] GeO2 has the effect of increasing the refractive index and resistance to devitrification of glass, but if its content is too high, the chemical stability of the glass decreases; on the other hand, compared with other components, the price of GeO2 is very expensive. From the perspective of glass raw material cost, its usage should be minimized. Therefore, the content of GeO2 in the present invention is limited to 0-4%, preferably 0-2%, more preferably 0-1%, and further preferably does not contain GeO2. In some embodiments, 0%, greater than 0%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4% GeO2 may be included.
[0058] In some embodiments, controlling the ratio of the Y2O3 content to the total content of Gd2O3, Ta2O5, ZnO, WO3, and GeO2, Y2O3 / (Gd2O3+Ta2O5+ZnO+WO3+GeO2) in the range of 0.9 to 4.0 can increase the bubble degree and striation degree of the glass and reduce the density of the glass. Therefore, the preferred Y2O3 / (Gd2O3+Ta2O5+ZnO+WO3+GeO2) is 0.9~4.0, the more preferred Y2O3 / (Gd2O3+Ta2O5+ZnO+WO3+GeO2) is 1.0~3.5, the further preferred Y2O3 / (Gd2O3+Ta2O5+ZnO+WO3+GeO2) is 1.0~3.0, and the further preferred Y2O3 / (Gd2O3+Ta2O5+ZnO+WO3+GeO2) is 1.2~2.0. In some embodiments, the value of Y2O3 / (Gd2O3+Ta2O5+ZnO+WO3+GeO2) may be 0.9, 0.95, 1.0, 1.05, 1.1, 1.15, 1.2, 1.25, 1.3, 1.35, 1.4, 1.45, 1.5, 1.55, 1.6, 1.65, 1.7, 1.75, 1.8, 1.85, 1. 9, 1.95, 2.0, 2.05, 2.1, 2.15, 2.2, 2.25, 2.3, 2.35, 2.4, 2.45, 2.5, 2.55, 2.6, 2.65, 2.7, 2.75, 2.8, 2.85, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0.
[0059] RO (RO is one or more of MgO, CaO, SrO and BaO) can improve the meltability of glass and adjust the optical constants of glass. If its content exceeds 5%, the devitrification resistance of glass decreases. Therefore, the content of RO in the present invention is 0 to 5%, preferably 0 to 3%, and more preferably 0 to 1%. In some embodiments, it is further preferred that MgO, CaO, SrO, and BaO are not contained. In some embodiments, RO may be included at 0%, greater than 0%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, or 5%. In some embodiments, 0%, greater than 0%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% MgO may be included. In some embodiments, 0%, greater than 0%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% CaO may be included. In some embodiments, 0%, greater than 0%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% SrO may be included. In some embodiments, BaO may be included at 0%, greater than 0%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, or 5%.
[0060] In some embodiments, the ratio (Ta2O5+ZnO+RO) / TiO2 between the total content of Ta2O5, ZnO, and RO and the content of TiO2 is controlled to be less than 2.5, so that the glass striation degree can be optimized while reducing the thermal expansion coefficient and density of the glass. Therefore, it is preferred that (Ta2O5+ZnO+RO) / TiO2 is less than 2.5, more preferably (Ta2O5+ZnO+RO) / TiO2 is less than 1.5, further preferably (Ta2O5+ZnO+RO) / TiO2 is less than 1.0, and further preferably (Ta2O5+ZnO+RO) / TiO2 is less than 0.5. In some embodiments, the value of (Ta2O5+ZnO+RO) / TiO2 may be 0, greater than 0, 0.01, 0.03, 0.05, 0.07, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1.0, 1.05, 1.1, 1.15, 1.2, 1.25, 1.3, 1.35, 1.4, 1.45, 1.5, 1.55, 1.6, 1.65, 1.7, 1.75, 1.8, 1.85, 1.9, 1.95, 2.0, 2.05, 2.1, 2.15, 2.2, 2.25, 2.3, 2.35, 2.4, 2.45, 2.5.
[0061] Rn2O (Rn2O is one or more of Li2O, Na2O, and K2O) can lower the transition temperature of glass, adjust the optical constants and high temperature viscosity of glass, and improve the melting property of glass. However, if its content is too high, the devitrification resistance and chemical stability of glass will decrease. Therefore, the content of Rn2O in the present invention is 0 to 5%, preferably 0 to 3%, and more preferably 0 to 1%. In some embodiments, it is further preferred that Li2O and / or Na2O and / or K2O are not contained. In some embodiments, 0%, greater than 0%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% Rn2O may be included. In some embodiments, 0%, greater than 0%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% Li2O may be included. In some embodiments, 0%, greater than 0%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% Na2O may be included. In some embodiments, KO may include 0%, greater than 0%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%.
[0062] In the present invention, by containing 0-1% of one or more components of Sb2O3, SnO2, and CeO2 as a clarifier, the clarification effect of the glass can be improved, and the bubble degree of the glass can be improved. The content of the clarifier is preferably 0-0.5%, and the content of the clarifier is more preferably 0-0.1%. Since the component types and contents of the optical glass of the present invention are reasonably designed and its bubble degree is excellent, it is further preferred that no clarifier is contained in some embodiments. When the content of Sb2O3 exceeds 1%, the glass tends to have reduced clarification performance. At the same time, due to its strong oxidizing effect, it promotes the corrosion of platinum or platinum alloy vessels for melting glass and the deterioration of the molding mold. Therefore, the present invention preferably contains 0-1% of Sb2O3, more preferably 0-0.5%, further preferably 0-0.1%, and further preferably does not contain Sb2O3. SnO2 can also be used as a clarifier, but when its content exceeds 1%, the tendency of glass coloring increases, or when the glass is heated, softened, and molded again, Sn will become the starting point of crystal nucleation, resulting in a tendency to devitrification. Therefore, the content of SnO2 in the present invention is preferably 0-1%, more preferably 0-0.5%, further preferably 0-0.1%, and further preferably does not contain SnO2. The function and content of CeO2 are consistent with those of SnO2, and its content is preferably 0-1%, more preferably 0-0.5%, further preferably 0-0.1%, and further preferably does not contain CeO2. In some embodiments, 0%, greater than 0%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% of clarifier may be included. In some embodiments, 0%, greater than 0%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% Sb2O3 may be included. In some embodiments, 0%, greater than 0%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% SnO2 may be included. In some embodiments, CeO2 may include 0%, greater than 0%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, or 1%.
[0063] <Components that should not be contained>
[0064] In the glass of the present invention, even if oxides of transition metals such as V, Cr, Mn, Fe, Co, Ni, Cu, Ag and Mo are contained alone or in combination in small amounts, the glass will be colored and absorption will occur at specific wavelengths in the visible light region, thereby weakening the property of the present invention of improving the visible light transmittance. Therefore, it is preferably substantially free of oxides of transition metals such as V, Cr, Mn, Fe, Co, Ni, Cu, Ag and Mo, especially for optical glasses that require transmittance at wavelengths in the visible light region.
[0065] The oxides of Th, Cd, Tl, Os, Be and Se have a tendency to be controlled in recent years as harmful chemical substances, and environmental protection measures are necessary not only in the manufacturing process of glass, but also in the processing process and the disposal after productization. Therefore, in the case of paying attention to the impact on the environment, it is preferred that they are not actually contained except for being inevitably mixed in. Thus, the optical glass does not actually contain substances that pollute the environment. Therefore, even if special environmental countermeasures are not taken, the optical glass of the present invention can be manufactured, processed and discarded.
[0066] In order to achieve environmental friendliness, the optical glass of the present invention preferably does not contain As2O3 and PbO.
[0067] The "does not contain" and "0%" recorded in this article mean that the compound, molecule or element is not intentionally added as a raw material to the optical glass of the present invention; however, as raw materials and / or equipment for producing optical glass, there will be certain impurities or components that are not intentionally added, which will be contained in a small amount or trace amount in the final optical glass, and this situation is also within the scope of protection of the patent of this invention.
[0068] Next, the properties of the optical glass of the present invention will be described.
[0069] <Refractive Index and Abbe Number>
[0070] The refractive index of optical glass (n d ) and the Abbe number (ν d ) Tested according to the method specified in GB / T 7962.1-2010.
[0071] In some embodiments, the refractive index (n d ) has a lower limit of 1.86, a preferred lower limit of 1.87, and a more preferred lower limit of 1.875.
[0072] In some embodiments, the refractive index (n d ) is 1.91, preferably 1.90, and more preferably 1.89.
[0073] In some embodiments, the Abbe number (ν d ) has a lower limit of 37, a preferred lower limit of 38, and a more preferred lower limit of 38.5.
[0074] In some embodiments, the Abbe number (ν d ) has an upper limit of 41, a preferred upper limit of 40.5, and a more preferred upper limit of 40.
[0075] <Coefficient of Thermal Expansion>
[0076] Thermal expansion coefficient of optical glass (α -30 / 70℃ ) The data at -30℃~70℃ were tested according to the method specified in GB / T7962.16-2010.
[0077] In some embodiments, the thermal expansion coefficient (α -30 / 70℃ ) is 85×10 -7 / K or less, preferably 80×10 -7 / K or less, more preferably 75×10 -7 / K or less.
[0078] <Water resistance stability>
[0079] Water resistance stability of optical glass (D W ) (Powder method) Tested in accordance with the method specified in GB / T 17129.
[0080] In some embodiments, the water resistance stability (D W ) is 2 or more types, preferably 1 type.
[0081] <Acid resistance stability>
[0082] Acid resistance stability of optical glass (D A ) (Powder method) Tested in accordance with the method specified in GB / T 17129.
[0083] In some embodiments, the acid resistance stability (D A ) is 2 or more types, preferably 1 type.
[0084] <Knoop hardness>
[0085] Knoop hardness of optical glass (H K ) is tested according to the test method specified in GB / T7962.18-2010. In the present invention, Knoop hardness is sometimes referred to as hardness.
[0086] In some embodiments, the Knoop hardness (H K) is 680×10 7 Pa or more, preferably 690×10 7 Pa or more, more preferably 700×10 7 Pa or above.
[0087] <Relative partial dispersion and relative partial dispersion deviation value>
[0088] The relative partial dispersion (P g,F ) and relative partial dispersion deviation (ΔP g,F ) origin.
[0089] The relative partial dispersion for wavelengths x and y is expressed by the following equation (1):
[0090] P x,y =(n x -n y ) / (n F -n C ) (1)
[0091] According to the Abbe number formula, for most so-called "normal glasses" (H-K6 and F4 are selected as "normal glasses" below), the following formula (2) is valid:
[0092] P x,y =m x,y ·v d +b x,y (2)
[0093] This linear relationship is based on P x,y is the vertical coordinate, v d It is represented by the horizontal axis, where m x,y is the slope, b x,y is the intercept.
[0094] As is known to all, the correction of the secondary spectrum, i.e. the achromatization of more than two wavelengths, requires at least one glass that does not conform to the above formula (2) (i.e. its P x,y The deviation value deviates from Abbe's empirical formula), and its deviation value is expressed as ΔP x,y If it is expressed, then each P x,y -v d The point is shifted by ΔP relative to the "normal line" that conforms to the above formula (2) x,y Quantity, so that the ΔP of each glass x,y The value can be obtained using the following formula (3):
[0095] P x,y =m x,y ·v d +b x,y +ΔP x,y (3)
[0096] Therefore, ΔP x,y It quantitatively represents the deviation characteristics of special dispersion compared with "normal glass".
[0097] Therefore, the relative partial dispersion (P g,F ) and relative partial dispersion deviation (ΔP g,F ) is calculated as follows (4) and (5):
[0098] P g,F =(n g -n F ) / (n F -n C ) (4)
[0099] ΔP g,F =P g,F -0.6457+0.001703v d (5)
[0100] In some embodiments, the relative partial dispersion (P g,F ) is 0.7000 or less, preferably 0.6500 or less, and more preferably 0.6000 or less.
[0101] In some embodiments, the relative partial dispersion deviation value (ΔP g,F ) is -0.0020 or less, preferably -0.0040 or less, more preferably -0.0050 or less, and further preferably -0.0058 or less.
[0102] <Bubble Degree>
[0103] The bubble degree of optical glass is tested according to the method specified in GB / T7962.8-2010.
[0104] In some embodiments, the bubble degree of the optical glass of the present invention is above grade A, preferably above grade A0, and more preferably above grade A1. 00 class.
[0105] <Striation Degree>
[0106] The streak degree of optical glass is checked by comparing with the standard sample from the direction where the streaks are most easily seen using a streak meter composed of a point light source and a lens. It is divided into 4 levels, as shown in Table 1 below.
[0107] Table 1. Streak level table
[0108] level Streak degree A No visible streaks under specified testing conditions B There are fine and scattered stripes under the specified test conditions C Slightly parallel streaks under specified test conditions D Rough parallel stripes under specified test conditions
[0109] In some embodiments, the striae of the optical glass of the present invention is C level or higher, preferably B level or higher.
[0110] <density>
[0111] The density (ρ) of optical glass is tested according to the method specified in GB / T7962.20-2010.
[0112] In some embodiments, the density (ρ) of the optical glass of the present invention is 5.10 g / cm 3 Below, preferably 5.00 g / cm 3 Below, more preferably 4.95g / cm 3 the following.
[0113] <Anti-crystallization performance>
[0114] The method for testing the anti-crystallization performance of the optical glass of the present invention is as follows: a glass sample of 10 mm × 20 mm × 20 mm size is placed in a semicircular porcelain box with a radius of 15 mm and a depth of 15 mm, and the glass sample and the porcelain box are placed in a T g The first heating was carried out in a test furnace at +230°C for 12 minutes, and then the temperature was lowered to 200°C in a tunnel annealing furnace; then the temperature was stabilized at T g The second heating was carried out in a test furnace at +230℃ for 12 minutes, and then the sample was taken out and cooled to 200℃ in a tunnel annealing furnace; then the sample was placed in a set holding temperature to stabilize at T g The third heating is carried out in a test furnace at +230℃ for 12 minutes. After the third heating, the glass sample and the porcelain box are placed in a tunnel annealing furnace and cooled to 200℃. After the glass sample is taken out, it is naturally cooled to room temperature in the atmosphere. After the glass sample is ground and polished, the overall softening degree and devitrification of the glass are observed with the naked eye, and the inside of the glass is observed under a microscope to confirm the presence of crystallization particles. The anti-crystallization performance of the glass is judged according to Table 2 below, with grade A being the best and grade E being the worst.
[0115] Table 2. Classification and judgment criteria of anti-crystallization performance
[0116]
[0117] In some embodiments, the anti-crystallization performance of the optical glass of the present invention is above Class C, preferably above Class B, and more preferably Class A.
[0118] [Method for producing optical glass]
[0119] The manufacturing method of the optical glass of the present invention is as follows: the glass of the present invention is produced using conventional raw materials and processes, including but not limited to using oxides, hydroxides, complex salts (such as carbonates, nitrates, sulfates, etc.), boric acid, etc. as raw materials, and after the ingredients are prepared according to the conventional method, the prepared furnace materials are put into a melting furnace (such as platinum or platinum alloy crucible) at 1200-1500°C for melting, and after clarification and homogenization, a homogeneous molten glass without bubbles and undissolved substances is obtained, and the molten glass is cast in a mold and annealed. Those skilled in the art can appropriately select raw materials, process methods and process parameters according to actual needs.
[0120] [Glass preforms and optical components]
[0121] The prepared optical glass can be used to make a glass preform by means of direct drop molding, grinding, or compression molding such as hot press molding. That is, the molten optical glass can be directly precision drop molded into a glass precision preform, or the glass preform can be made by mechanical processing such as grinding and grinding, or the preform for compression molding made of the optical glass can be made by hot press molding and then grinding. It should be noted that the means for preparing the glass preform are not limited to the above means.
[0122] As described above, the optical glass of the present invention is useful for various optical elements and optical designs, and it is particularly preferred to form a preform from the optical glass of the present invention and use the preform to perform re-hot pressing, precision stamping, etc. to produce optical elements such as lenses and prisms.
[0123] The glass preform and optical element of the present invention are both formed of the optical glass of the present invention. The glass preform of the present invention has the excellent properties of optical glass; the optical element of the present invention has the excellent properties of optical glass, and can provide various optical elements such as lenses and prisms with high optical value.
[0124] Examples of the lens include various lenses having spherical or aspherical lens surfaces, such as a concave meniscus lens, a convex meniscus lens, a biconvex lens, a biconcave lens, a plano-convex lens, and a plano-concave lens.
[0125] [Optical instruments]
[0126] The optical element formed by the optical glass of the present invention can be used to manufacture optical instruments such as photographic equipment, video equipment, projection equipment, display equipment, vehicle-mounted equipment and monitoring equipment.
[0127] Example
[0128] <Optical Glass Example>
[0129] In order to further clearly illustrate and describe the technical solution of the present invention, the following non-limiting examples are provided.
[0130] This embodiment adopts the above optical glass manufacturing method to obtain optical glasses having the compositions shown in Tables 3 to 5. In addition, the properties of each glass are measured by the testing method described in the present invention, and the measurement results are shown in Tables 3 to 5.
[0131] Table 3.
[0132]
[0133]
[0134] Table 4.
[0135]
[0136]
[0137] Table 5.
[0138]
[0139]
[0140] <Glass Preform Example>
[0141] The glass obtained from optical glass examples 1 to 21# is used, for example, by grinding processing, or by molding methods such as hot pressing, precision stamping, etc., to make preforms of various lenses, prisms, etc., such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses.
[0142] <Optical Element Embodiment>
[0143] The preforms obtained in the above-mentioned glass preform embodiments are annealed to reduce the internal stress of the glass and fine-tune the refractive index so that the optical properties such as the refractive index reach the desired values.
[0144] Next, each preform is ground and polished to produce various lenses and prisms such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses. The surface of the obtained optical element may be coated with an anti-reflection film.
[0145] <Optical Instrument Embodiment>
[0146] The optical element obtained by the above-mentioned optical element embodiment is optically designed to form an optical component or optical assembly by using one or more optical elements, and can be used in, for example, imaging equipment, sensors, microscopes, medical technology, digital projection, communications, optical communication technology / information transmission, optics / lighting in the automotive field, lithography technology, excimer lasers, wafers, computer chips, and integrated circuits and electronic devices including such circuits and chips.
Claims
1. Optical glass, characterized in that: Its components, expressed in weight percentage, include: SiO2: 4-11%; B2O3: 8-15%; La2O3: greater than 45% but less than or equal to 55%; Gd2O3: 2-9.5%; Y2O3: 4-10%; ZrO2: 3-10%; Nb2O5: 5-12%; TiO2: 0.1-5%; Al2O3: greater than 0 but less than or equal to 4%, among which Al2O3 / TiO2 is 0.05-3.0, (TiO2+ZnO+Ta2O5+WO3) / Nb2O5 is 0.01-1.0, and Y2O3 / (Gd2O3+Ta2O5+ZnO+WO3+GeO2) is 1.2-4.
0.
2. The optical glass according to claim 1, characterized in that: Its components are expressed in weight percentage, and also contain: ZnO: 0-4%; and / or RO: 0-5%; and / or Rn2O: 0-5%; and / or WO3: 0-5%; and / or Ta2O5: 0-5%; and / or Yb2O3: 0-5%; and / or GeO2: 0-4%; and / or clarifier: 0-1%, wherein RO is one or more of MgO, CaO, SrO, and BaO, Rn2O is one or more of Li2O, Na2O, and K2O, and the clarifier is one or more of Sb2O3, SnO2, and CeO2.
3. Optical glass, characterized in that: Its components include SiO2, B2O3, La2O3, Gd2O3, Y2O3, ZrO2, Nb2O5, TiO2 and Al2O3, and its components are expressed in weight percentage, among which SiO2: 4-11%; B2O3: 8-15%; La2O3: greater than 45% but less than or equal to 55%; Gd2O3: 2-9.5%; Y2O3: 4-10%; ZrO2: 3-10%; N b2O5: 5-12%; TiO2: 0.1-5%; Al2O3: greater than 0 but less than or equal to 4%, Al2O3 / TiO2 is 0.05-3.0, (TiO2+ZnO+Ta2O5+WO3) / Nb2O5 is 0.01-1.0, Y2O3 / (Gd2O3+Ta2O5+ZnO+WO3+GeO2) is 1.2-4.0, and the Knoop hardness of the optical glass is H K 680×10 7 Pa or above, and the anti-crystallization performance is above Class C.
4. The optical glass according to claim 3, characterized in that: Its components are expressed in weight percentage, and also contain: ZnO: 0-4%; and / or RO: 0-5%; and / or Rn2O: 0-5%; and / or WO3: 0-5%; and / or Ta2O5: 0-5%; and / or Yb2O3: 0-5%; and / or GeO2: 0-4%; and / or clarifier: 0-1%, wherein RO is one or more of MgO, CaO, SrO, and BaO, Rn2O is one or more of Li2O, Na2O, and K2O, and the clarifier is one or more of Sb2O3, SnO2, and CeO2.
5. The optical glass according to any one of claims 1 to 4, characterized in that: Its components are expressed in weight percentage and meet one or more of the following 10 conditions: 1) Gd2O3 / Y2O3 is 0.25 to 1.1; 2) Gd2O3 / SiO2 is 0.2-1.0; 3) Al2O3 / TiO2 is 0.1-2.0; 4) (La2O3+Y2O3) / (Nb2O5+ZrO2) is 2.5-6.5; 5) Al2O3 / Gd2O3 is 0.02-0.8; 6) (La2O3+Nb2O5) / Gd2O3 is 6.0 to 23.0; 7) Nb2O5 / Y2O3 is 0.6 to 2.0; 8) Al2O3 / SiO2 is 0.01 to 0.8; 9) (TiO2+ZnO+Ta2O5+WO3) / Nb2O5 is 0.05-0.8; 10) (Ta2O5+ZnO+RO) / TiO2 is less than 2.5, The RO is one or more of MgO, CaO, SrO and BaO.
6. The optical glass according to any one of claims 1 to 4, characterized in that: Its components are expressed in weight percentage and meet one or more of the following 11 conditions: 1) Gd2O3 / Y2O3 is 0.3-1.0; 2) Gd2O3 / SiO2 is 0.3-0.95; 3) Al2O3 / TiO2 is 0.1-1.5; 4) (La2O3+Y2O3) / (Nb2O5+ZrO2) is 2.8-6.0; 5) Al2O3 / Gd2O3 is 0.05-0.6; 6) (La2O3+Nb2O5) / Gd2O3 is 8.0-20.0; 7) Nb2O5 / Y2O3 is 0.7 to 1.7; 8) Al2O3 / SiO2 is 0.05-0.6; 9) Y2O3 / (Gd2O3+Ta2O5+ZnO+WO3+GeO2) is 1.2~3.5; 10) (TiO2+ZnO+Ta2O5+WO3) / Nb2O5 is 0.1-0.5; 11) (Ta2O5+ZnO+RO) / TiO2 is less than 1.5, The RO is one or more of MgO, CaO, SrO and BaO.
7. The optical glass according to any one of claims 1 to 4, characterized in that: Its components are expressed in weight percentage and meet one or more of the following 11 conditions: 1) Gd2O3 / Y2O3 is 0.4 to 0.9; 2) Gd2O3 / SiO2 is 0.4 to 0.9; 3) Al2O3 / TiO2 is 0.2-1.0; 4) (La2O3+Y2O3) / (Nb2O5+ZrO2) is 3.0-5.5; 5) Al2O3 / Gd2O3 is 0.1 to 0.5; 6) (La2O3+Nb2O5) / Gd2O3 is 9.0-15.0; 7) Nb2O5 / Y2O3 is 0.8 to 1.5; 8) Al2O3 / SiO2 is 0.08-0.5; 9) Y2O3 / (Gd2O3+Ta2O5+ZnO+WO3+GeO2) is 1.2~3.0; 10) (TiO2+ZnO+Ta2O5+WO3) / Nb2O5 is 0.1-0.3; 11) (Ta2O5+ZnO+RO) / TiO2 is less than 1.0, The RO is one or more of MgO, CaO, SrO and BaO.
8. The optical glass according to any one of claims 1 to 4, characterized in that: Its components are expressed in weight percentage and meet one or more of the following 9 conditions: 1) Gd2O3 / Y2O3 is 0.5 to 0.9; 2) Gd2O3 / SiO2 is 0.5 to 0.9; 3) (La2O3+Y2O3) / (Nb2O5+ZrO2) is 3.5-5.0; 4) Al2O3 / Gd2O3 is 0.1-0.4; 5) (La2O3+Nb2O5) / Gd2O3 is 10.0~13.0; 6) Nb2O5 / Y2O3 is 0.9 to 1.2; 7) Al2O3 / SiO2 is 0.1 to 0.3; 8) Y2O3 / (Gd2O3+Ta2O5+ZnO+WO3+GeO2) is 1.2~2.0; 9) (Ta2O5+ZnO+RO) / TiO2 is less than 0.5, The RO is one or more of MgO, CaO, SrO and BaO.
9. The optical glass according to any one of claims 1 to 4, characterized in that: Its components are expressed in weight percentage, wherein: SiO2: 5-10%; and / or B2O3: 10-14%; and / or La2O3: 46-53%; and / or Gd2O3: 3-8%; and / or Y2O3: 5-9.5%; and / or ZrO2: 4-9%; and / or Nb2O5: 5.5-11%; and / or TiO2: 0.5-4%; and / or Al2O3: 0.1-3%; and / or ZnO: 0-2%; and / or RO: 0~3%; and / or Rn2O: 0~3%; and / or WO3: 0~3%; and / or Ta2O5: 0~3%; and / or Yb2O3: 0~3%; and / or GeO2: 0~2%; and / or clarifier: 0~0.5%, wherein RO is one or more of MgO, CaO, SrO, and BaO, Rn2O is one or more of Li2O, Na2O, and K2O, and the clarifier is one or more of Sb2O3, SnO2, and CeO2.
10. The optical glass according to any one of claims 1 to 4, characterized in that: Its components are expressed in weight percentage, wherein: SiO2: 5.5-9%; and / or B2O3: 11-13.5%; and / or La2O3: 48-52%; and / or Gd2O3: 4-7%; and / or Y2O3: 5.5-8.5%; and / or ZrO2: 5-8%; and / or Nb2O5: 6-10%; and / or TiO2: 1-3%; and / or Al2O3: 0.5-2%; and / or ZnO: 0-1%; and / or RO: 0~1%; and / or Rn2O: 0~1%; and / or WO3: 0~1%; and / or Ta2O5: 0~1%; and / or Yb2O3: 0~1%; and / or GeO2: 0~1%; and / or clarifier: 0~0.1%, wherein RO is one or more of MgO, CaO, SrO, and BaO, Rn2O is one or more of Li2O, Na2O, and K2O, and the clarifier is one or more of Sb2O3, SnO2, and CeO2.
11. The optical glass according to any one of claims 1 to 4, characterized in that: Its components do not contain ZnO; and / or do not contain MgO; and / or do not contain CaO; and / or do not contain SrO; and / or do not contain BaO; and / or do not contain Li2O; and / or do not contain Na2O; and / or do not contain K2O; and / or do not contain WO3; and / or do not contain Ta2O5; and / or do not contain Yb2O3; and / or do not contain GeO2; and / or do not contain Sb2O3; and / or do not contain SnO2; and / or do not contain CeO2.
12. The optical glass according to any one of claims 1 to 4, characterized in that: The refractive index n of the optical glass d 1.86~1.91; Abbe number v d It is 37 to 41.
13. The optical glass according to any one of claims 1 to 4, characterized in that: The refractive index n of the optical glass d 1.87~1.90; Abbe number v d It is 38 to 40.
5.
14. The optical glass according to any one of claims 1 to 4, characterized in that: The refractive index n of the optical glass d 1.875~1.89; Abbe number v d It is 38.5~40.
15. The optical glass according to any one of claims 1 to 4, characterized in that: The thermal expansion coefficient of the optical glass is α -30 / 70℃ 85×10 -7 / K or less; and / or water resistance stability D W Class 2 or above; and / or acid resistance stability D A Class 2 or above; and / or Knoop hardness H K 680×10 7 Pa or above; and / or relative partial dispersion P g,F is less than 0.7000; and / or relative partial dispersion deviation value ΔP g,F is -0.0020 or less; and / or the bubble degree is A or above; and / or the striae degree is C or above; and / or the density ρ is 5.10 g / cm 3 and / or the anti-crystallization performance is C grade or above.
16. The optical glass according to any one of claims 1 to 4, characterized in that: The thermal expansion coefficient of the optical glass is α -30 / 70℃ 80×10 -7 / K or less; and / or water resistance stability D W Class 1; and / or acid resistance stability D A Class 1; and / or Knoop hardness H K 690×10 7 Pa or above; and / or relative partial dispersion P g,F is less than 0.6500; and / or relative partial dispersion deviation value ΔP g,F is -0.0040 or less; and / or the bubble degree is A0 or above; and / or the striae degree is B or above; and / or the density ρ is 5.00g / cm 3 and / or the anti-crystallization performance is B grade or above.
17. The optical glass according to any one of claims 1 to 4, characterized in that: The thermal expansion coefficient of the optical glass is α -30 / 70℃ 75×10 -7 / K or less; and / or Knoop hardness H K 700×10 7 Pa or above; and / or relative partial dispersion P g,F is less than 0.6000; and / or relative partial dispersion deviation value ΔP g,F is below -0.0050; and / or the bubble degree is A 00 Grade; and / or density ρ is 4.95g / cm 3 Below; and / or anti-crystallization performance is Class A.
18. The optical glass according to any one of claims 1 to 4, characterized in that: The relative partial dispersion deviation value ΔP of the optical glass g,F It is below -0.0058.
19. A glass preform, characterized in that: Made of the optical glass described in any one of claims 1 to 18.
20. An optical element, characterized in that The optical glass is made of the optical glass described in any one of claims 1 to 18, or the glass preform described in claim 19.
21. An optical instrument, characterized in that Contains the optical glass according to any one of claims 1 to 18, and / or contains the optical element according to claim 20.
Citation Information
Patent Citations
High-refractive index and low-dispersion heavy lanthanum flint optical glass
CN106927676A
Optical glass
CN115321814A
Optical glass and optical element
CN115385569A
Optical glass with high refractive index
CN115385570A
Optical glass, glass preform, optical element and optical instrument
CN117658445A